Researching social space in social work institutions. A case study on a women's shelter - Marc Diebäcker; Anna Fischlmayr; Aurelia Sagmeister (Social Work and Society)
The initial point of our research project was to find out, if our findings match our observation that despite the important role institutional spaces - in which social services, professional support and the service users' everyday lives are highly interlinked - play in professional social work practice, they are still not subject to a specific scientific discourse. Additionally, we assumed that an analytical perspective on social space inside social work facilities is hardly formulated, let alone published. In this article we present the outcomes of a two year-long research project, in which we analysed social interactions in their relation to social space in three social work facilities, using an ethnographic qualitative approach. The following article will present results from a case study on a women's shelter for women and children who have become victims of domestic violence, run by the association"wendepunkt" in Lower Austria. Our findings show how social work facilities can serve as"places of refuge" or"safe spaces" for their users, what strategies and patterns of behaviour people develop in order to appropriate space, as well as how social relations between users and staff evolve. The way borders, thresholds and permeabilities between the institutional inside and the outside world are processed, tells us a lot about how the social orders inside the facilities are interrelated with societal processes of exclusion. In the case of women's shelters this interrelation can be reflected in its origins as feminist movements, societal constructions of insecurity in the public space (in contrast to the reality of insecure private spaces their addressees experience) and patriarchal structures in society, state and family. The research approach we used and describe in the article proved to be a promising possibility to better grasp social work in its institutional frame and its socio-spatial relations. Especially organisations and facilities, in which professional settings highly intertwine with the users' everyday life, could benefit from this approach.